Etiology of Early-Onset Neonatal Sepsis and Antibiotic Resistance in Bukavu, Democratic Republic of the Congo. (12th February 2021) - Mulinganya, Guy M; Claeys, Maud; Balolebwami, Serge Z; Bamuleke, Bertrand A; Mongane, Jules I; Boelens, Jerina; Delanghe, Joris; De Vos, Daniel; Kambale, Richard M; Maheshe, Ghislain B; Mateso, Guy M; Bisimwa, Ghislain B; et al.
Abstract: Background: The Democratic Republic of the Congo (DRC) has one of the highest neonatal death rates (between 14% and 28%) in the world. In the DRC, neonatal sepsis causes 15.6% of this mortality, but data on the bacterial etiology and associated drug susceptibility are lacking. Methods: Hemocultures of 150 neonates with possible early-onset neonatal sepsis (pEOS) were obtained at the Hôpital Provincial Général de Référence de Bukavu (Bukavu, DRC). The newborns with pEOS received an empirical first-line antimicrobial treatment (ampicillin, cefotaxime, and gentamicin) based on the synopsis of international guidelines for the management of EOS that are in line with World Health Organization (WHO) recommendations. Isolates were identified using matrix-assisted laser desorption/ ionization time-of-flight mass spectrophotometry. Antibiotic resistance was assessed using the disk diffusion method. Results: Fifty strains were obtained from 48 patients and identified. The 3 most prevalent species were Enterobacter cloacae complex (42%), Klebsiella pneumoniae (18%), and Serratia marcescens (12%). Enterobacter cloacae isolates were resistant to all first-line antibiotics. All K. pneumoniae and S. marcescens isolates were resistant to ampicillin, and the majority of the K. pneumoniae and half of the S. marcescens isolates were resistant to both cefotaxime and gentamicin. All E. cloacae complex strains, 89% of K. pneumoniae, and half of S. marcescens had an extended-spectrum ß-lactamase phenotype. Conclusions: The most prevalent pathogens causing EOS in Bukavu were E. cloacae complex, K. pneumoniae, and S. marcescens . Most of these isolates were resistant to the WHO-recommended antibiotics. Abstract : The early-onset neonatal sepsis case fatality rate was 25.3% among hospitalized neonates in Bukavu. Enterobacter cloacae, Klebsiella pneumoniae, and Serratia marcescens were the pathogens most commonly retrieved. A total of 100%, 88.9%, and 86.1% of these isolates were resistant to ampicillin, cefotaxime, and gentamicin, respectively.